Clinical and MRI results after microfracture of osteochondral lesions of the talus - Kuni, Benita; Schmitt, Holger; Chloridis, Dimitrios; Ludwig, Karl (Archives of orthopaedic and trauma surgery, 2012)
Purpose: Arthroscopic microfracture (AM) of osteochondral lesions of the talus is used to induce intrinsic refilling of the defect and reduce pain. The aim of this retrospective study was to investigate the clinical state after AM and the MRI outcome. Methods: A total of 22 patients [10 women, 12 men, 31 years old (mean, 13-68 range)] treated for osteochondral lesions of the talus by AM were examined 2 years (median) postoperatively and pre- and postoperative MRI results compared. Swelling/effusion, articular constriction, joint pain, and range of motion restriction were documented. Clinical state was evaluated using the AOFAS hindfoot score. MRI was used to assess the size of the defect, presence of bone marrow edema, cysts and effusion, thickness of repair tissue, and integrity of the cartilage. Results: In all but six cases, the defect was located at the medial shoulder of the talus. The postoperative AOFAS score at follow-up was 87.5 points (median 36-100 points range). Seven patients were free of pain, 11 had “mild, occasional” pain, 1 “moderate daily”, and 3 “severe, almost always present” pain (AOFAS). The defect volume was significantly reduced from 377 mm3 preoperatively (median, interquartile distance: 417 mm3) to 249 mm3 postoperatively (median, IQD: 336 mm3, p = 0.019, Wilcoxon). In 7 cases, the defect was completely filled, in 11 partially and in 4 only slightly.Conclusion: After AM of osteochondral lesions of the talus, 18 of 22 patients had no or mild, occasional pain at 2 years follow-up. On MRI, the lesion volume had been reduced and filling with repair tissue was found.